DEVELOPING SCRABBLE GAME TO TEACH ENGLISH VOCABULARY FOR ELEMENTARY SCHOOL STUDENTS - Inayatul Fuad; Siti Rofi’ah; Widiarini Widiarini (UIBU, 2023)
In 2023, the media in the process of learning English is veryimportant. This is evidenced by a needs analysis with 26 students and teachers of English class V . This paper aims to investigate the needs of students and also find out the results of scrabble games on transportation, professions, weather and seasons. This study used the Borg & Gall Research and Development (R&D) model. It used several steps including Research & Information Gathering, Develop the initial form of the product, Revise the product, Product testing, Final product revision. The research subjects were 26 fifth grade students at SDN Gading Kasri Malang. This study found that scrabble games are valid in language (92%) and media (97%) and suitable for use as complementary media on transportation, profession, weather and season from the satisfaction questionnaire about this product the percentage is around 14% agree and 84% strongly agree. Finally, this scrabble game is suitable for use as a complement to material on transportation, professio